Targets downstream of Cdk8 in Dictyostelium development. - Greene, D; Bloomfield, G; Skelton, J; Ivens, A; Pears, C (BioMed Central, 2011)
Background: Cdk8 is a component of the mediator complex which facilitates transcription by RNA polymerase II and has been shown to play an important role in development of Dictyostelium discoideum. This eukaryote feeds as single cells but starvation triggers the formation of a multicellular organism in response to extracellular pulses of cAMP and the eventual generation of spores. Strains in which the gene encoding Cdk8 have been disrupted fail to form multicellular aggregates unless supplied with exogenous pulses of cAMP and later in development, cdk8- cells show a defect in spore production. Results: Microarray analysis revealed that the cdk8- strain previously described (cdk8-HL) contained genome duplications. Regeneration of the strain in a background lacking detectable gene duplication generated strains (cdk8-2) with identical defects in growth and early development, but a milder defect in spore generation, suggesting that the severity of this defect depends on the genetic background. The failure of cdk8- cells to aggregate unless rescued by exogenous pulses of cAMP is consistent with a failure to express the catalytic subunit of protein kinase A. However, overexpression of the gene encoding this protein was not sufficient to rescue the defect, suggesting that this is not the only important target for Cdk8 at this stage of development. Proteomic analysis revealed two potential targets for Cdk8 regulation, one regulated post-transcriptionally (4-hydroxyphenylpyruvate dioxygenase (HPD)) and one transcriptionally (short chain dehydrogenase/reductase (SDR1)). Conclusions: This analysis has confirmed the importance of Cdk8 at multiple stages of Dictyostelium development, although the severity of the defect in spore production depends on the genetic background. Potential targets of Cdk8-mediated gene regulation have been identified in Dictyostelium which will allow the mechanism of Cdk8 action and its role in development to be determined.